Time-driven activity-based costing in health care: A systematic review of the literature - Keel, George; Savage, Carl; Rafiq, Muhammad; Mazzocato, Pamela (Health policy (Amsterdam), 2017)
•TDABC helps to address the challenge of costing conditions in health care.•TDABC applications varied but generally reflected the seven-step model.•Future TDABC Applications should consider the methodological recommendations in this review.•TDABC is yet to overcome challenges with allocating support department costs.•TDABC’s ability to inform bundled payment reimbursement is not well established. Health care organizations around the world are investing heavily in value-based health care (VBHC), and time-driven activity-based costing (TDABC) has been suggested as the cost-component of VBHC capable of addressing costing challenges. The aim of this study is to explore why TDABC has been applied in health care, how its application reflects a seven-step method developed specifically for VBHC, and implications for the future use of TDABC. This is a systematic review following the PRISMA statement. Qualitative methods were employed to analyze data through content analyses. TDABC is applicable in health care and can help to efficiently cost processes, and thereby overcome a key challenge associated with current cost-accounting methods The method’s ability to inform bundled payment reimbursement systems and to coordinate delivery across the care continuum remains to be demonstrated in the published literature, and the role of TDABC in this cost-accounting landscape is still developing. TDABC should be gradually incorporated into functional systems, while following and building upon the recommendations outlined in this review. In this way, TDABC will be better positioned to accurately capture the cost of care delivery for conditions and to control cost in the effort to create value in health care.